KRITIK ULAMA HADIS KONTEMPORER TERHADAP HADIS-HADIS TANPA STATUS DI DALAM RIYĀḌ AL-ṢĀLIḤĪN - Faridi, Faridi; Setiadi, Ayi; Reftiyani, Annisa; Ridwan, Ahmad Fauzi; Andi, Andi (Jurnal Studi Hadis Nusantara, 2024)
The explanation of the status of a hadith is very important, especially if the mentioned hadith is not accompanied by a complete chain of transmission. This is particularly relevant in today's context, where not everyone possesses the ability to trace hadith and assess their authenticity. In Riyāḍ al-Ṣāliḥīn, there are thirty-eight hadiths whose status al-Nawawī did not evaluate or mention, except for merely citing their sources. This motivated the author to clarify the status of these thirty-eight hadiths to the public, enabling them to distinguish between accepted and rejected hadiths. The author employed the library research method, utilizing qualitative data obtained by searching for the Book of Riyāḍ al-Ṣāliḥīn through the Shamela Book Library application and referring to the research findings of three contemporary hadith scholars, such as Muḥammad Nāṣiruddīn al-Albānī, Syu'aib al-Arnā’uṭ, and Alī bin Nāyif al-Syuḥūd. Among these thirty-eight hadiths, twenty hadiths had their validity agreed upon, five hadiths were unanimously considered weak, and thirteen hadiths remained subjects of dispute.